Terceirização e trabalhadores da construção civil na cidade de Araraquara/SP - Scavichia, Gloriete Santos [UNESP] (2015)
The transformations in work in the universe are affecting intensely to industrial societies around the world, so that the restructuring of productive activities, including technological innovations and new management of the workforce resulting in a significant increase in rates productivity, profound changes in the relationship between companies and ways of organizing production, interfering in labor relations and negotiations with the institutions that protect workers. This research aims to analyze the flexibility of labor relations, embodied in labor outsourcing process in the economic segment construction in Araraquara / SP. Therefore, we propose an initial analysis of the Fordist / Taylorist production techniques, to understand the process of flexibility of labor relations as currently at present. In this context, outsourcing is particularly important for portraying one of the ways that best portrays the world of flexible working, with all the implications inherent to them, especially the weakening of workers' rights. To do this we chose the construction segment to accomplish our study, because it is a strongly marked by sector manpower outsourcing, and bring complexities inherent in the activity. From the empirical research conducted on construction sites of two construction of Araraquara / SP, we see many faces of outsourcing, which makes it even more complex the topic at hand and encourages research in this area